Cutaneous hyperpigmentation as a diagnostic marker of vitamin B12 deficiency: a case report - Henshaw, Eshan B.; Okafor, Love E.; Ekpenyong, Henry J. (International Journal of Research in Dermatology, 2022)
Cutaneous hyperpigmentation and glossitis are recognized but often overlooked early signs of vitamin B12 deficiency (VB12D). Pernicious anaemia is the most common cause of VB12D. Many clinicians miss the diagnosis of this potentially fatal but treatable condition in the absence of the more often reported life-threatening neuropsychiatric and haematologic features, notwithstanding the concomitant presence of characteristic cutaneous signs. These apperceptions of conspicuous and early dermatologic signs lead to diagnostic delay, which can result in dire consequences for the patient. We report the case of a 24-year-old young woman who for two years had repeated blood transfusions, iron supplementation and haematinics on account of anaemia of undetermined aetiology of a yet to be determined aetiology, despite the simultaneous presence of a constellation of glaring dermatologic clues to vitamin B12 deficiency. Following diagnosis and the institution of the appropriate therapy, the patient made remarkable improvement with a reversal of pigmentation and correction of the anaemia within a month. She continues to see the haematologists for follow-up.